Morfometrik dan Meristik Ikan Gobi di Sungai Bone, Gorontalo - Kadim, Miftahul Khair; Antonio Sinulingga, Luis; Pasisingi, Nuralim; Ibrahim Miolo, Mikhael (Jurnal Sumberdaya Akuatik Indopasifik, 2024)
Scientific information on Goby fish species in Gorontalo waters is still not widely available. Nike is a local term used by Gorontalo local people for larvae and juvenile schools of gobies. This fish has important economic value for the Gorontalo area and has been designated a provincial communal Intellectual Property Right. Limited information regarding the existence and importance of this fish in Gorontalo waters is a challenge for sustainable management of nike fish resources. One aspect that needs to be reported in this regard is the morphometrics and meristics of the adult Nike Stadia. This research aimed to provide data on morphometric and meristic differences in Gobi fishes in the Bone River. This research was carried out in November 2021, while sample identification was conducted at the Fisheries Hydrobiotechnology and Biometrics Laboratory, Faculty of Fisheries and Marine Sciences, Gorontalo State University. The Image-J application carried out Sample morphometric measurements, while the meristic data was observed directly. The results showed that the morphometrics and meristics of the gobi species (Sicyopterus longifilis, Belobranchus belobranchus, and Bunaka gyrinoides) from Bone River differed.